Pengaruh Penggunaan Model Pembelajaran Berbasis Proyek (Project-Based Learning) Terhadap Hasil Belajar Peserta Didik Pada Materi Litosfer Dalam Pembelajaran Geografi Kelas X Di SMA Negeri 3 Gorontalo Utara - Putri, Putri (-, 2025)
The aim of this study is to examine the impact of the Project-Based Learning (PjBL) model on the learning outcomes of class X students on lithosphere material at SMA Negeri 3 Gorontalo Utara. This research was conducted during the even semester of the 2024/2025 academic year, utilizing a quasi-experimental approach with a Nonequivalent Control Group Design. The study involved two groups: an experimental group taught using the PjBL model and a control group taught using the Discovery Learning model. The research instrument was a 20-item multiple-choice test, which was validated and tested for reliability. The data collected were analyzed using SPSS version 30, employing tests for validity, reliability, normality, homogeneity, and t-tests. The analysis revealed that the data followed a normal distribution and were homogeneous. The t-test results showed a significance value of 0.003, which is smaller than the significance level of 0.05, indicating that the PjBL model significantly influences student learning outcomes. The experimental group demonstrated a greater improvement in learning outcomes compared to the control group. These findings are expected to contribute to the development of learning strategies and serve as a reference for future research.